Redescription and first Japanese seamount record of Stethopristes eos (Zeiformes; Parazenidae) - Koeda, Keita; Sado, Tetsuya; Hata, Harutaka; Fujiwara, Yoshihiro (Zootaxa, 2024)
During a biodiversity survey conducted in 2020, focusing on seamounts located in the southern region of Japan, specifically designated as marine protected areas, a single specimen of Stethopristes eos Gilbert, 1905 measuring 124.2 mm in standard length was obtained via the use of a remotely operated vehicle (ROV). The collection occurred at a depth of 519 meters on the Ritto Seamount, located along the western Mariana Ridge. However, this species is poorly known, with only a limited dataset available concerning its morphology. In this study, we present a comprehensive redescription of the species, utilizing information obtained from the type specimens and a newly discovered specimen from Japanese waters. The Japanese specimen constitutes the first recorded occurrence of this species within the western Pacific Ocean. As part of this redescription, we suggest new standard Japanese names for both the genus and species.